Анализ и оценка альтернатив - Воронин, А.Н. (Проблемы управления и информатики, 2013)
Показано, що при векторному підході задача прийняття рішень шляхом декомпозиції властивостей альтернатив репрезентується ієрархічною системою критеріїв. На нижчому рівні ієрархії здійснюється оцінка альтернативи за окремими властивостями за допомогою вектора критеріїв, а на верхньому рівні застосуванням механізму композиції отримуємо оцінку альтернативи у цілому. Задача розв’язується методом вкладених скалярних згорток. Методологія розв’язання задачі ґрунтується на принципі додатковості Бора та теоремі про неповноту Геделя. It is shown, that under vector approach a decision-making problem through the alternatives properties decomposition is presented by a hierarchical system of criteria. At the bottom level of hierarchy the estimation of the alternative by separate properties is carried out by means of a vector of criteria, and at the top level by means of the mechanism of the composition the estimation of the alternative as a whole is obtained. The problem is solved by the method of nested scalar convolutions of vector-valued criteria. The methodology of the problem solving is based on N. Bohr complementarity principle and K. Gödel theorem of incompleteness.